NK cells converge lytic granules to promote cytotoxicity and prevent bystander killing - Hsu, Hsiang-Ting (J Cell Biol, 2016)
Natural killer (NK) cell activation triggers sequential cellular events leading to destruction of diseased cells. We previously identified lytic granule convergence, a dynein- and integrin signal–dependent movement of lysosome-related organelles to the microtubule-organizing center, as an early step in the cell biological process underlying NK cell cytotoxicity. Why lytic granules converge during NK cell cytotoxicity, however, remains unclear. We experimentally controlled the availability of human ligands to regulate NK cell signaling and promote granule convergence with either directed or nondirected degranulation. By the use of acoustic trap microscopy, we generated specific effector–target cell arrangements to define the impact of the two modes of degranulation. NK cells with converged granules had greater targeted and less nonspecific “bystander” killing. Additionally, NK cells in which dynein was inhibited or integrin blocked under physiological conditions demonstrated increased nondirected degranulation and bystander killing. Thus, NK cells converge lytic granules and thereby improve the efficiency of targeted killing and prevent collateral damage to neighboring healthy cells.